PENGARUH KOMPOS JERAMI PADI DANFOSFOR TERHADAP PERTUMBUHAN DANPRODUKSI TANAMAN JAGUNG (Zeamays L.) DI LAHAN GAMBUT - Randa Efrian; Murniati Murniati; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study aims to determine the effect of rice straw compost and fosfor and get the best combination on the growth and yield of corn. This research has been carried out in the Agrotechnology Education Garden of the Faculty of Agriculture, University of Riau, located in Rimbo Panjang Village, Tambang District, Kampar Regency, Riau Province. The study was conducted for 5 months starting from February 2018 until June 2018. The research was conducted experimentally in the form of factorial 3 x 4 using a Randomized Block Design (RBD). Factor 1 of rice straw compost consists of 3 levels (5, 10,15 tons.ha-1) and factor 2 of fosfor fertilizer consists of 4 levels (48, 96, 144,192 kg.ha-1) and 3 replications. Data obtained from the results of the study were statistically analyzed using variance to determine the effect of treatment, and the results of variance were continued with Duncan New Multiple Range Test at 5% level to determine differences between treatments. The results showed that the dose of rice straw compost and fosfor fertilizer had different effects on plant growth and yield. The application of 10 tons.ha-1 rice straw compost and 144 kg.ha-1 P fertilizer is the bestdose to increase the growth and yield of corn. Keywords : rice straw compost, fosfor, corn plants.